Financial Ratios and Profit Growth: Evidence from Bank BNI During COVID-19 - Gani Wiharso; Wahid Akbar Basudani; Ratna Puspita; Johan Hendri Prasetyo (Institute of Computer Science (IOCS), 2026)
This study examines the effect of financial ratios, namely Loan to Deposit Ratio LDR, Debt to Equity Ratio DER, and Return on Assets ROA, on profit growth at Bank BNI over the period 2016 to 2025, covering pre, during, and post COVID 19 phases. Prior studies largely rely on short term observations and overlook crisis periods, limiting understanding of financial ratio performance under economic disruption. This study addresses this gap by providing longitudinal evidence in a crisis context. A quantitative causal approach was applied using multiple linear regression. The results show that LDR has a negative and insignificant effect on profit growth with a coefficient of negative 15.603 and a significance value of 0.102. DER also exhibits a negative and insignificant effect with a coefficient of negative 0.594 and a significance value of 0.587, while ROA shows a positive but insignificant relationship with a coefficient of 4.820 and a significance value of 0.926. Simultaneous testing indicates that all variables do not significantly affect profit growth with an F value of 1.664 and a significance level of 0.272. The model explains 45.4 percent of the variation in profit growth, although the adjusted R square of 0.181 suggests limited explanatory power. These findings highlight the limited role of financial ratios in explaining profit growth during economic uncertainty. The study contributes by providing crisis based longitudinal evidence and implies the need to incorporate broader determinants in performance evaluation